Design as an interactive boundary object - Thinley Tharchen; Raghu Garud; Rebecca L. Henn (Journal of Organization Design, 2020)
What is it about the term~"design" that facilitates the emergence of interdisciplinary interactions even though the term may hold different meanings for those involved? To address this question, we analyzed the vocabularies, practices and orders of worth ~proposed by the members of an interdisciplinary Center for Design. Our analysis revealed similarities and differences in the meanings accorded by these individuals to the term design. The analysis also revealed an~awareness on their part that their notions of design were incomplete, and that they had to rely on the inputs of others. Such~reflexivity was an important factor in fostering meaningful interactions between these individuals. Based on these findings, we argue that design is an interactive boundary object, which enables different meaning structures to co-exist and co-inform actors from multiple disciplines and domains. Within such a view, the emergence of interactions occurs not despite but because of the diversity of views about the notion of design itself.
Keywords: 650; Design; Vocabularies; Practices; Orders of worth; Design games; Reflexivity; Interactive boundary object